Co-occurrence of and factors associated with health risk behaviors among adolescents: a multi-center study in sub-Saharan Africa, China, and India - Li, Xuan; Dessie, Yadeta; Mwanyika-Sando, Mary; Assefa, Nega; Millogo, Ourohiré; Manu, Adom; Chukwu, Angela; Bukenya, Justine; Patil, Rutuja; Zou, Siyu; Zhang, Hanxiyue; Nurhussien, Lina; et al. (EClinicalMedicine, 2024)
Background - Despite lifelong and detrimental effects, the co-occurrence of health risk behaviors (HRBs) during adolescence remains understudied in low- and middle-income countries. This study examines the co-occurrence of HRBs and its correlates among adolescents in sub-Saharan Africa, China, and India. - Methods - A multi-country cross-sectional study was conducted in 2021-2022, involving 9697 adolescents (aged 10-19 years) from eight countries, namely Burkina Faso, China, Ethiopia, India, Ghana, Nigeria, Tanzania, and Uganda. A standardized questionnaire was administered to examine five types of HRBs − physical inactivity, poor dietary habits, smoking, alcohol consumption, and risky sexual behavior. Latent class analysis was employed to identify clustering patterns among the behaviors, and logistic regression was used to identify the correlates of these patterns. - Findings - Three clusters of HRBs were identified, with Cluster 1 (27.73%) characterized by the absence of any specific risky behavior, Cluster 2 (68.16%) characterized by co-occurrence of physical inactivity and poor dietary habits, and Cluster 3 (4.11%) characterized by engagement in smoking, alcohol consumption, and risky sexual behavior. Relative to Cluster 1, being in Cluster 2 was associated with being female (aOR 1.20, 95% CI 1.09-1.32), not enrolled in education (aOR 0.84, 95% CI 0.71-0.99), and not engaged in paid work (aOR 1.23, 95% CI 1.08-1.41). Compared with those Cluster 1, adolescents in Cluster 3 were less likely to be female (aOR 0.41, 95% CI 0.32-0.54), be engaged in paid work (aOR 0.54, 95% CI 0.41-0.71), more likely to be older (aOR 7.56, 95% CI 5.18-11.03), not be enrolled in educational institution (aOR 1.74, 95% CI 1.27-2.38), and more likely to live with guardians other than parents (aOR 1.56, 95% CI 1.19-2.05). - Interpretation - The significant clustering patterns of HRBs among adolescents in sub-Saharan Africa, China, and India highlights the urgent need for convergent approaches to improve adolescent health behaviors. Early life and school-based programs aimed at promoting healthy behaviors and preventing risky and unhealthy behaviors should be prioritized to equip adolescents with the tools and skills for lifelong well-being. - Funding - Fondation Botnar (Grant #INV-037672) and Harvard T.H. Chan School of Public Health, partially funded this study.